Increased hip fracture risk in the patients with type 2 diabetes mellitus is correlated with urine albumin-to-creatinine ratio (ACR) and diabetes duration in men - Huiru Ding; Huiru Ding; Hongxia Wang; Hongxia Wang; Guanghui Liu; Yu Wang; Yu Wang; Dongxu Han; Dongxu Han; Xiaoya Zhang; Xiaoya Zhang; Lige Song; et al. (Experimental Biology and Medicine)
Patients with type 2 diabetes mellitus (T2DM) have increased hip fracture risk. And the association between urine albumin to creatinine ratio (ACR) and an increased risk of hip fracture in patients with T2DM remains controversial. This study aimed to investigate the association between urinary ACR and hip fracture risk in postmenopausal women and aged men with T2DM. The study included 219 postmenopausal women and 216 older men (mean age >60 years) with T2DM. Women and men were divided into control group (ACR<30 mg/g), microalbuminuria group (30 mg/g ≤ ACR<300 mg/g), and macroalbuminuria group (ACR≥300 mg/g) respectively. Demographic characteristics and clinical history were collected in patients. Biochemical indexes and bone turnover-related markers were measured in patients. In the study, we found that several factors, including age, T2DM duration, cerebral infarction history, serum corrected calcium levels and urine ACR were positively associated with hip fracture risk. However, 25-Hydroxyvitamin D and areal BMD were negatively associated with hip fracture risk. Furthermore, multiple regression analysis showed that urinary ACR level (β = 0.003, p = 0.044) and duration of T2DM (β = 0.015, p = 0.018) were positively and independently correlated with hip fracture risk in older men. In contrast, femoral neck BMD (β = −6.765, p < 0.001) was independently and negatively correlated with hip fracture risk in older men. This study indicated that the elevated ACR levels and longer T2DM duration were related to higher hip fracture risk in older men with T2DM, which could be beneficial for developing a predictive model for osteoporotic fractures in patients with type 2 diabetes in the future. However, results were inconsistent in women, hip fracture risk didn’t alter by changes in urinary microalbuminuria level in postmenopausal women with T2DM.